Bile Acid Tethered Docetaxel‐Based Nanomicelles Mitigate Tumor Progression through Epigenetic Changes. (19th January 2021) - Sreekanth, Vedagopuram; Kar, Animesh; Kumar, Sandeep; Pal, Sanjay; Yadav, Poonam; Sharma, Yamini; Komalla, Varsha; Sharma, Harsh; Shyam, Radhey; Sharma, Ravi Datta; Mukhopadhyay, Arnab; Sengupta, Sagar; et al.
Abstract: In this study, we describe the engineering of sub‐100 nm nanomicelles (DTX‐PC NMs) derived from phosphocholine derivative of docetaxel (DTX)‐conjugated lithocholic acid (DTX‐PC) and poly(ethylene glycol)‐tethered lithocholic acid. Administration of DTX‐PC NMs decelerate tumor progression and increase the mice survivability compared to Taxotere (DTX‐TS), the FDA‐approved formulation of DTX. Unlike DTX‐TS, DTX‐PC NMs do not cause any systemic toxicity and slow the decay rate of plasma DTX concentration in rodents and non‐rodent species including non‐human primates. We further demonstrate that DTX‐PC NMs target demethylation of CpG islands of Sparcl1 (a tumor suppressor gene) by suppressing DNA methyltransferase activity and increase the expression of Sparcl1 that leads to tumor regression. Therefore, this unique system has the potential to improve the quality of life in cancer patients and can be translated as a next‐generation chemotherapeutic. Abstract : Phosphocholine derivative of docetaxel‐conjugated lithocholic acid can form stable sub‐100 nm nanomicelles (DTX‐PC NMs). DTX‐PC NMs exhibit superior tolerance and pharmacokinetics over FDA‐approved formulation. DTX‐PC NMs can retard tumor progression in murine models and induce upregulation of tumor suppressor genes. Superior pharmacokinetic profiling in non‐human primates makes them an ideal platform for clinical applications.